2017
DOI: 10.1371/journal.pone.0177609
|View full text |Cite
|
Sign up to set email alerts
|

Impressive predictive value of ankle-brachial index for very long-term outcomes in patients with cardiovascular disease: IMPACT-ABI study

Abstract: BackgroundThe ankle—brachial index (ABI) is a marker of generalized atherosclerosis and is predictive of future cardiovascular events. However, few studies have assessed its relation to long-term future cardiovascular events, especially in patients with borderline ABI. We therefore evaluated the relationship between long-term future cardiovascular events and ABI.MethodsIn the IMPACT-ABI study, a single-center, retrospective cohort study, we enrolled 3131 consecutive patients (67 ± 13 years; 82% male) hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The Ankle-Brachial Index (ABI) is a simple and non-invasive tool used to diagnose Peripheral arterial disease (PAD). An ABI of <0.9 has been considered abnormal and has been not only associated with the diagnosis of PAD, but has been also a marker of incident cardiovascular events and mortality in both symptomatic and asymptomatic forms of PAD [17]. It has been repeatedly associated with a three to six times greater risk of cardiovascular events and mortality [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ankle-Brachial Index (ABI) is a simple and non-invasive tool used to diagnose Peripheral arterial disease (PAD). An ABI of <0.9 has been considered abnormal and has been not only associated with the diagnosis of PAD, but has been also a marker of incident cardiovascular events and mortality in both symptomatic and asymptomatic forms of PAD [17]. It has been repeatedly associated with a three to six times greater risk of cardiovascular events and mortality [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies carried out in countries with high and low rates of cardiovascular disease have detected a high incidence of cardiovascular events and mortality in patients with PAD [17].…”
Section: Introductionmentioning
confidence: 99%
“…The IMPACT-ABI study showed that the incidence of stroke was significantly higher in the low ABI (≤0.9) and borderline ABI (0.91–0.99) than those with normal ABI (1.00–1.40) in patients hospitalized for cardiovascular disease during a 4.8-year mean follow-up period. 25 In the study of surveillance of cardiovascular events in antiplatelet-treated arteriosclerosis obliterans patients in Japan (SEASON), Miyata et al. found that those with ABI < 0.9 had a significantly higher risk of any vascular events (including cerebrovascular and cardiovascular events) and all-cause death compared to normal ABI.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies described that the score of ABI tended to be higher in HD patients than Non-HD cohort. 20,21 Therefore, there is a possibility that our Non-PAD groups in our study might include several PAD patients, if we conducted the image test to them in detail. However, it is important that our results are derived by non-invasive and simple examination, and the present association between PAD and frailty, such as the lower grip strength and smaller thigh circumference values in patients with PAD was not changed according to the definition of PAD as ABI <1.0.…”
Section: Discussionmentioning
confidence: 99%